A Conceptual Framework Based on Maturana’S Ontology of the Observer to Explore the Checkland’S Soft Systems Methodology - Jerardino-Wiesenborn, B (Springer, 2020)
This paper explores Checkland’s Soft Systems Methodology (SSM) through the lenses of a theoretical framework that incorporates key concepts from Maturana’s Ontology of the Observer (OoO) with the view of complementing Checkland’s SSM application process. We outline and examine paradigmatic compatibility between: Checkland’s ontological position (reality is problematic/chaotic) together with his interpretivist epistemology (multiple perceptions enrich the ever-changing reality); and Maturana’s OoO (we are immersed in the praxis of living in an ontological multi-universe). We argue that OoO resonates with key SSM theoretical underpinnings. After establishing compatibility between these two influential systems thinkers, we advance a conceptual framework in which Checkland’s SSM learning process is re-visited through a the framework grounded on Maturana’s OoO. The proposed framework illustrates how key ideas drawn from Maturana’s OoO can shed light into the way in which some of the main SSM devices (i.e.: Root definitions, Conceptual model) are used in the SSM process. By doing that, SSM is enriched and becomes more flexible as the stakeholders involved are placed within the domain of constitutive ontologies from which, a deeper dialogue can be promoted in a domain of coexistence in mutual acceptance. We argue that this is a suitable way to have more flexible and holistic views for a SSM intervention in particular to promote the learning process and debating proposed changes amongst the stakeholders involved. The proposed framework, when applied, may enhance the power of SSM learning process and when adopted can have substantial implications to complement the SSM process. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Problem structuring; Systemic learning; Soft systems methodology; Ontology of the observer; Multi-methodology